Bioética, medicamentos, conflicto de intereses y control de calidad - La Rosa Rodríguez, Emilio (2012)
Bioethics, medicines, interests conflict and quality controlThe article analyzes the problems of pharmaceutical advertising that distorts, exaggerates or hides certain information (side effects of drugs), as well as the work of pharmaceutical sales  representatives, the problem of drugs’ risk, marketing authorization, access to drugs, therapeutic practice, conflicts of interest, and quality control in medicine. These issues have a greater importance in public health; since the lack of respect for the fundamental principles of bioethics (benefit, not harm, autonomy and consent) has a direct impact on the health of the population.